2017
DOI: 10.1080/21632324.2016.1159887
|View full text |Cite
|
Sign up to set email alerts
|

Do remittances and social assistance have different impacts on expenditure patterns of recipient households? The Moldovan Case

Abstract: Do remittances and social assistance have different impacts on household expenditure patterns? While two separate strands of literature have looked at how social assistance or remittances have been spent, few studies have compared them directly. Using data from a nationally representative household survey conducted in Moldova in 2011, this paper assesses the impact both types of transfers have on household expenditure patterns. Contrary to the common assumption that money is fungible, we find that social assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
4
0
5
Order By: Relevance
“…When looking at the magnitude of the impact, however, remittances appear to have a larger poverty reduction effect, most likely due to a higher level of the transfer and the fact that in these specific case studies remittances are better targeted at poor households. In addition, Waidler et al (2016) compared the effects of remittances and social grants on expenditure patterns in Moldova and concluded that public and private transfers were not spent in the same way.…”
Section: Comparing the Effects Of Social Grants And Remittancesmentioning
confidence: 99%
“…When looking at the magnitude of the impact, however, remittances appear to have a larger poverty reduction effect, most likely due to a higher level of the transfer and the fact that in these specific case studies remittances are better targeted at poor households. In addition, Waidler et al (2016) compared the effects of remittances and social grants on expenditure patterns in Moldova and concluded that public and private transfers were not spent in the same way.…”
Section: Comparing the Effects Of Social Grants And Remittancesmentioning
confidence: 99%
“…Acerca de las características económicas y sociales asociadas al hogar, se advierten discrepancias relevantes entre grupos: los hogares que reciben remesas presentan un mayor número de dependientes económicos. A su vez, los hogares receptores de remesas son en promedio más propensos a recibir beneficios del programa Oportunidades, lo cual podría invitar a pensar que las transferencias públicas y privadas son complementarias y no sustitutas, como lo explican Waidler et al (2017). Además, las características socioeconómicas adicionales indican que los hogares receptores de remesas se concentran en deciles de ingresos más bajos comparados con los no receptores.…”
Section: B Estadísticas Descriptivasunclassified
“…At the empirical front, the welfare effects of remittances have been widely investigated. Petreski and Jovanovic (2013) make extensive reference to this strand of the literature: some papers date back to 1987, like Lucas, while others are quite recent, for example, Waidler et al (2017), suggesting that the topic of remittances has not lost of its appeal over the decades. However, the potential of remittances to act as informal social protection and insurance mechanisms in a broader sense has rarely been investigated.…”
Section: Literature Reviewmentioning
confidence: 99%